The road to success: the case of Perak state Islamic religious council - S. Noor-Kaziemah; M. Rozaidy; Raman Noordin; Rasid Mail; Nur Shahida Ab Fatah (Academic Inspired Network, 2021)
State Islamic Religious Councils (SIRCs) was established with the purpose to manage Muslim affairs in Malaysia, especially for the underprivileged group through improving their social and economic welfare. Many criticisms were addressed by the public and media on how well the SIRCs function and manage their finance. The critics do not come empty without evidence of the real mismanagement cases reported by the public auditors and media. As scandals are prone to invite negative perceptions from the public, it also eclipses the organisations’ achievements by hyperbolically concentrating on the negative stories. As a result, most literature related to the SIRCs has majorly focused on discussing the issues rather than reporting both sides of the stories, the issues or challenges and the achievements of the SIRCs. Hence, throughout the years, the SIRCs have been striving in improving their performances through engaging with many fruitful initiatives, which subsequently enhance the SIRCs’ ability to productively serve the Muslim community. The outcomes from the improvements can be seen in many awards and recognitions received by the SIRCs. Highlighting the achievements of the SIRCs will not only increase the positive perceptions but motivate other SIRCs to follow the same footsteps. Thus, the objective of this paper is to discuss both sides of the stories, i.e. challenges and achievements of Perak SIRC. The paper starts with an introduction of the roles and functions of Perak SIRC, then highlights the challenges of Perak SIRC in carrying out its roles and continues with a discussion of the efforts undertaken to improve their operations and the achievements gained through the effort. The study utilises a case study method. The study found that Perak SIRC has a long history (since 1874) and has achieved many milestones and awards for their excellent performance.